PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DI UPT SMP NEGERI 1 KELARA KABUPATEN JENEPONTO - Israwati Resky; Nurindah; Firdaus Rahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Development of Canva-Based Learning Media in Natural Science Subjects for Grade VII Students at UPT SMP Negeri 1 Kelara, Jeneponto Regency. This study aims to develop Canva-based learning media. The development model used in this study is the ADDIE Model. The results of this study are a product in the form of Canva-based learning media. The results of the media validation analysis obtained 3,6 with a valid assessment category, the results of the material validation obtained 3,57 with a valid assessment category, and the results of student responses in the trial conducted obtained an average score of 4.19 with an interesting assessment category. Student responses, validator responses in developing Canva-based learning media in Natural Science subjects for grade VII at UPT SMP Negeri 1 Kelara, Jeneponto Regency are said to be feasible and good to use in the learning process as a means that can help improve the quality of learning and facilitate understanding of the material by students. This is because Canva-based learning media is very simple, easy to access anywhere and anytime, presents images, animations and is practical.